Assessing the Training Needs Regarding ‘Breaking Bad News’ amongst Emergency Medical Services (EMS) Professionals in Pune India - Parag Rishipathak1, Shrimathy Vijayaraghavan2, Dr. Anand Hinduja3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction:‘Breaking Bad News’ (BBN) in the scenario of poor prognosis or death is considered to beone of the most stressful aspects of the duties of a Healthcare professional. In the recent years, the subject ofBBN has gained traction among healthcare professionals and psychologist leading to the creation of somecomprehensive models to train professionals. Emergency Medical Professionals are among the likeliest toencounter BBN situations. Hence it is imperative that they be formally trained to deal with patients and theirfamilies effectivelyObjective: To assess the training needs regarding ‘Breaking Bad News’ (BBN); amongst EmergencyMedical Services (EMS) Professionals.Methodology: The study was conducted amongst 150 Emergency Medical Professionals in Pune, India. Apreviously tested and validated questionnaire developed by Rasmus etal in June 2020 was utilized for thestudy. Questionnaire was administered to the respondents through online mode after obtaining informedconsent. Responding to all questions was mandatory. The respondents were given one day to fill thequestionnaire. Any queries pertaining to questionnaire were clarified during data collection.Discussion: The present study was done to assess the baseline awareness of EMS professionals about BBNand to devise a customized training program for them. Unfortunately, majority of the respondents werenot even aware that BBN is a separate subject having specific procedures and protocols followed globally.The lack of training instils fear of facing such situations and adversely affects the mental health of EMSprofessionals. This can be corrected by utilizing tools like simulation and role play to provide adequateexposure to EMS professionals in a safe environment.Conclusion: The findings of the study point towards an emergent need of formal practical training on thiscrucial yet ignored aspect of the health care professionals’ duties. Comparative Studies can be conducted inthe future to assess the effectiveness of this training program.